2023
DOI: 10.1177/23727322221144647
|View full text |Cite
|
Sign up to set email alerts
|

Heart Rate Variability Biofeedback for Mental Health Treatment: A Policy Brief

Abstract: The WHO argues that a pharmacy-first approach should no longer be the reflexive treatment for mental health diagnoses. Heart rate variability biofeedback (HRVB) demonstrably treats various conditions—especially effective at regulating emotion, particularly managing and alleviating anger, stress, anxiety, and depression, common co-morbid diagnoses for rehabilitation medicine patients. HRVB trains users to study their biofeedback data in real time, alter bodily functions previously believed to be automatic, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Given that RESE-NE is a malleable cognitive structure relatively easy to target in interventions (see Bandura, 1997), self-efficacy seems a promising avenue for helping workers dealing with high neuroticism levels. Likewise, HRV could also be directly targeted, as past research has shown that meditation practices as well as slow breathing exercises could improve HRV and cardiac activity (for a meta-analysis, see Laborde et al, 2022; Shearer et al, 2016), as well as biofeedback training (Kim, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Given that RESE-NE is a malleable cognitive structure relatively easy to target in interventions (see Bandura, 1997), self-efficacy seems a promising avenue for helping workers dealing with high neuroticism levels. Likewise, HRV could also be directly targeted, as past research has shown that meditation practices as well as slow breathing exercises could improve HRV and cardiac activity (for a meta-analysis, see Laborde et al, 2022; Shearer et al, 2016), as well as biofeedback training (Kim, 2023).…”
Section: Discussionmentioning
confidence: 99%